Disrupsi Profesi Akuntan Di Era Revolusi Industri 4.0 - Mahbubah, Istiyanatul; Putri, Sofie Yunida (Wacana Equiliberium (Jurnal Pemikiran Penelitian Ekonomi), 2020)
This research discusses the disruption of the Accountant Profession in the Era of the Industrial Revolution 4.0, with the aim of analyzing the threats and opportunities of Industrial Revolution 4.0 for the existence of the accountant profession and how to deal with it, in the 4.0 industrial revolution there were very significant changes in various sciences and professions, so that they were able to disrupt the profession. Accountant. This study used a qualitative method with a phenomenological approach, with data collection techniques through semi-structured interviews with both informants. Based on the results of interviews with the two informants, it can be seen that massive use of technology is one of the biggest impacts of disruption. The two informants also expressed the same opinion that the most important thing an accountant must have in the era of the industrial revolution 4.0 at this time is the figure of an accountant who is able to prepare himself to master technology and be ready to face the various changes and technological developments that accompany it.